TRANSFORMASI PENDIDIKAN ISLAM MENUJU SOCIETY 5.0: ANALISIS KURIKULUM DAN KOMPETENSI GURU - Arif Rahman Hakim; Zulaekah (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This article examines the transformation of Islamic education towards Society 5.0, focusing on two main aspects: curriculum and teacher competence. The Society 5.0 era demands an education system that integrates technology with humanistic values, where Islamic education must adapt to the changing times without neglecting the moral and ethical dimensions that are integral to Islamic teachings. This study employs a descriptive qualitative approach to analyze the Islamic education curriculum and teacher competence in Madrasah Aliyah and private Islamic schools that have implemented technology-based learning. The findings indicate that although several institutions have attempted to integrate technology, its use in learning is still limited to material delivery and has not been fully optimized to develop critical and creative thinking skills. Moreover, the competence of Islamic Religious Education teachers in utilizing technology needs to be strengthened through more intensive training. The Islamic education curriculum needs to undergo transformation to accommodate students' needs in mastering 21st-century skills while continuing to reinforce character based on Islamic values. The study concludes that the development of an adaptive curriculum and the continuous enhancement of teacher competence are key to realizing relevant Islamic education in the Society 5.0 era.